Mesospheric plasma irregularities caused by the missile destruction on 9 December 2009. Issue 6 (13th June 2017) - Kozlovsky, Alexander; Shalimov, Sergey; Lester, Mark
Abstract: On 9 December 2009 at about 07 UT a solid propellant 36.8 t ballistic rocket was self‐destroyed at an altitude of 170–260 km, at a distance of about 500 km to the east of Sodankylä Geophysical Observatory (SGO, 67°22′N, 26°38′E, Finland). After 2–3 h the SGO meteor radar (operating at a frequency 36.9 MHz) received unusual echoes, which indicate turbulence of ionospheric plasma (irregularities of electron density) with a temporal scale on the order of 0.1 s and a spatial scale of a few to tens of meters. The turbulence occurred at a height of about 80 km and was localized in several areas of about 60 km in horizontal scale. Line‐of‐sight velocity of the irregularities was up to a few tens of meters per second toward the radar. The event occurred in the winter high‐latitude mesosphere during extremely low solar and geomagnetic activity. Aerosol particles caused by the missile explosion played a key role in producing the electron density irregularities. As a possible explanation, we suggest that sedimented by gravity and, hence, moving with respect to the air, charged aerosol particles (presumably composed of aluminum oxide) might produce meter‐scale irregularities (electrostatic waves) via dissipative instability, which is a mechanism analogous to that of the resistive beam‐plasma instability. Key Points: Solid propellant rocket destruction in the ionosphere on 9 December 2009 VHF meteor radar detected electron density irregularities caused by dust of the rocket remains in the mesosphere Dust‐associated mesospheric irregularities with a temporal scale of 0.1 s and a spatial scale of a few to tens of meters